Longitudinal Analysis of the Relationships Between Social Support and Health-Related Quality of Life in Hematopoietic Stem Cell Transplant Recipients. Issue 3 (May 2019) - Liang, Yongchun; Wang, Haifang; Niu, Meie; Zhu, Xiaming; Cai, Jianzheng; Wang, Xiubei
Abstract : Background: The correlation between social support and health-related quality of life (HRQOL) has been well documented, but whether social support changes or whether social support consistently plays a significant role in the various phases of the treatment process remains unknown among hematopoietic stem cell transplantation (HSCT) patients. Objectives: The aims of this study were to assess the changing trends of HRQOL and social support and evaluate the relationship between HRQOL and social support before and after transplantation. Methods: Measures were completed by 122 HSCT patients before and after transplantation. The measures administered included the Perceived Social Support Scale and the Functional Assessment of Cancer Therapy–Bone Marrow Transplant questionnaire. Results: The social support score presented a marked downward trend ( F = 17.090, P < .001). The overall HRQOL was the lowest, 103.61 (SD, 19.14) at 1 month and increased steadily over time to 108.10 (SD, 19.58) at 3 months and 110.02 (SD, 18.00) at 6 months after HSCT. The generalized estimating equation models showed that social support consistently had a positive impact on HRQOL in the 6-month period post-HSCT. Conclusion: We confirmed a significant positive association between social support and HRQOL in HSCT recipients. However, it is noteworthy that the social support score declined during the 6-month period even while the HRQOL scores were increasing. Implications for Practice: Social support is closely related to the HRQOL; thus, clinicians should give close attention to social support to improve the HRQOL of HSCT patients. Social support should not be overlooked during the first 6 months after transplantation.